In-situ electrochemical synthesis of a high-performance S/VOx composite for aqueous zinc ion batteries. (7th July 2022) - Deng, Lei; Yu, Dongxu; Sun, Ge; Zhang, Xinyuan; Wang, Chunzhong; Tian, Ruiyuan; Du, Fei
Abstract: V-based materials have attracted wide attention as high-capacity cathode materials for aqueous batteries owing to their unique structures. However, much effort should be made to increase the rate performance and solve the issue of fast capacity fading to meet the ever-growing need for low-cost and safe energy-storage devices. Herein, a novel S/VO x composite is synthesized via a very simple in-situ electrochemical-induced phase transition from VS4 . The as-prepared composite electrode can deliver an initial discharge capacity of 376 mAh g −1 at a current density of 0.05 A g −1, much higher than that of VS4 (150 mAh g −1 ). Moreover, it shows a good discharge capacity of 260 mAh g −1 at 2 A g −1 with a retention of ∼100% over 2000 cycles, indicating an impressive electrochemical stability. The outstanding Zn 2+ storage performance could be attributed to the characteristics of the composite's unique structure, highly reversible electrochemical reactions, and fast Zn 2+ transport.